Effect of Y addition on the microstructures and mechanical properties of Mg-Gd-Y-Sm-Zr alloys - Fu sanling; Li quanan; Chen Jun; Zhang Qing (Functional Materials, 2017)
The microstructure and mechanical properties of Mg–12Gd–xY–Sm–0.5Zr (x = 0, 1, 3, 5; mass%) alloys were investigated. Results showed β’-Mg5Gd phase composition evolution of Mg5(Gd,Y). The tensile strength of the alloys are better the WE54 alloy at high temperatures (200–300 °C). The optimal mechanical properties of the Mg-12Gd-3Y-1Sm-0.5Zr alloy are achieved at high temperatures, and the maximum tensile strength of this alloy is 323 MPa at 250 °C. The short heat-resisting performance of Mg–Gd–Y–Sm–Zr alloys under the high temperature will provide new scientific basis for the development of heat resistant magnesium alloys. Исследованы микроструктура и механические свойства сплавов Mg-12Gd-xY-Sm- 0.5Zr (x  = 0, 1, 5,%). Результаты показали, что фазовый состав β'-Mg5 Gd эволюционирует в Mg5 (Gd, Y). Прочность на растяжение этих сплавов лучше сплава WE54 при высоких температурах (200-300 °C). Оптимальные механические свойства сплава Mg-12Gd-3Y-1Sm- 0.5Zr достигаются при высоких температурах, а максимальная прочность на растяжение этого сплава составляет 323 МПа при 250 °C. Жаростойкие сплавы Mg-Gd-Y-Sm-Zr при высокой температуре станут новой научной основой для разработки термостойких магниевых сплавов. Досліджено мікроструктура і механічні властивості сплавів Mg-12Gd-xY-Sm-0.5Zr (x  = 0, 1, 5,%). Результати показали, що фазовий склад β’-Mg5 Gd еволюціонує в Mg5 (Gd, Y). Міцність на розтяг сплавів краще сплаву WE54 при високих температурах (200-300 °C). Оптимальні механічні властивості сплаву Mg-12Gd-3Y-1Sm-0.5Zr досягаються при високих температурах, а максимальна міцність на розтягнення цього сплаву становить 323 МПа при 250 °C. Жаростойкие сплави Mg-Gd-Y-Sm-Zr при високій температурі стануть новою науковою основою для розробки термостійких магнієвих сплавів.